Vector mechanics for engineers : Statics /Ferdinand P. Beer, E. Russell Johnston, Jr., Elliot R. Eisenberg ; with the collaboration of David F. Mazurek. : - Beer, Ferdinand P.(Ferdinand Pierre),1915-2003.
Includes index.